Analyzing the content of the mathematics textbook of the fifth grade preparatory according to the depth of knowledge levels - Khudhair, Laila Khalid; Jasim, A.S.D. Basim Mahammad (The journal of contemporary issues in business and government, 2021)
The aim of the current research is to identify the degree of availability of levels of depth of knowledge in the mathematics book for the fifth grade of the scientific and applied branch, the research sample consisted of the mathematics book of the tenth edition of the year 2019 of the fifth grade of the scientific branch of the application. To achieve the goal of the research, the two researchers prepared a list of levels of depth of mathematical knowledge. The recall, the level of concepts and skills, the level of strategic thinking and the level of extended thinking, the book was analyzed according to the aforementioned levels, using the analytical descriptive method and the stability of the analysis was confirmed by analyzing over time and individuals and the proportion of stability was 75% that was obtained by applying the Holste equation The results of the analysis of the book, as I have said: the percentage of availability of the level of recall reached (36.65%), the percentage of availability of the level of concepts and skills reached (31.78%), the percentage of availability of the level of strategic thinking reached (20.88%), the percentage of availability of the level of extended thinking reached (6710%).